Pengaruh Pelayanan, Harga, Dan Lokasi TerhadapLoyalitas Pelanggan Studi Kasus B-Prend Cafe(Survey Pada B-Prend Cafe di Kabupaten Rembang) - Anggriawan, Ferry, Basworo Dibyo, S.E, M.Si (2017)
This study is intended to analyze the influence of service, price, location, and also to analyze whether the service, price and location provide any significant effect on customer loyalty at B-prend Café. The Data was collected by throwing questions to the respondents with questionnaire guide. Random sampling technique was the sampling technique. The sample in this study was a questionnaire of service, price, location from 100 respondents as customers in Bprend Café. The results of analyzed data in this study were : 1) The Service Variable had significant and positive impact on customer loyalty. 2) The Price Variable had significant and negative effect on customer loyalty. 3) The Location Variable had significant and positive impact on customer loyalty. 4) The Service, Price, and Location Variable had significant effect on customer loyalty. 5) The coefficient determinant which contribute 58,9% between variables of service, price and location on customer loyalty are described by performance, price, and location variables of Customer Loyalty and the remaining 41.1% is described by other variables outside the model.